2017
DOI: 10.1038/s41598-017-08763-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of SE initial dedifferentiation in cotton of different SE capability

Abstract: Somatic embryogenesis (SE) is a critical transition from vegetative to embryogenic growth in higher plants; however, few studies have investigated the mechanism that regulates SE initial differentiation. Most cotton varieties have not undergone regeneration by SE, so only a few varieties can be used in genetic engineering. Here, two varieties of cotton with different SE capabilities (HD, higher differentiation and LD, lower differentiation) were analyzed by high throughout RNA-Seq at the pre-induction stage (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 62 publications
(71 reference statements)
1
43
0
Order By: Relevance
“…Auxin response factor (ARFs) is considered as essential SE genes that are specifically activated during embryogenic differentiation [31][32][33][34]. ARFs bind auxin response promoter elements, mediate transcriptional responses to auxin and regulate auxin-mediated transcriptional activation/repression, together with Aux/IAA [35,36]. Three repetitions of the biological experiments were performed.…”
Section: Candidate Gene Expression Pattern Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxin response factor (ARFs) is considered as essential SE genes that are specifically activated during embryogenic differentiation [31][32][33][34]. ARFs bind auxin response promoter elements, mediate transcriptional responses to auxin and regulate auxin-mediated transcriptional activation/repression, together with Aux/IAA [35,36]. Three repetitions of the biological experiments were performed.…”
Section: Candidate Gene Expression Pattern Validationmentioning
confidence: 99%
“…Some of the identified genes have been experimentally demonstrated to play an important role in SE [29,35,43,44]. Somatic embryogenesis receptor kinase (SERK) is involved in the signal transduction pathway during somatic embryogenesis and is a marker gene for the embryotic state.…”
Section: Photosynthesis Cell Cycle and Serk Pathway During Somatic Ementioning
confidence: 99%
“…With the release of the C. canephora genome (Denoeud et al, 2014 The RNA-Seq technology has allowed us to have a complete picture of the genes expressed during SE induction. Transcriptomic studies have showed that the most important and determining changes begin at the start of the SE induction stage (1 DAI) and at the beginning of the development of the first structures (21 DAI) or, in other words, at the moment of the shift from a non-embryogenic state to an embryogenic one (Cheng et al, 2016;Shi et al, 2016;Tao et al, 2016;Cao et al, 2017;Chu et al, 2017;Enríquez-Valencia et al, 2019). Cao et al (2017) identified the main regulation phase of SE initiation in cotton to occur between three hours and three days after induction.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptomic studies have showed that the most important and determining changes begin at the start of the SE induction stage (1 DAI) and at the beginning of the development of the first structures (21 DAI) or, in other words, at the moment of the shift from a non-embryogenic state to an embryogenic one (Cheng et al, 2016;Shi et al, 2016;Tao et al, 2016;Cao et al, 2017;Chu et al, 2017;Enríquez-Valencia et al, 2019). Cao et al (2017) identified the main regulation phase of SE initiation in cotton to occur between three hours and three days after induction. As is the case in our results, most of the dramatic changes are visualized during the transition from the pre-conditioning stage to the first hours of the induction stage and the 21 DAI where embryogenic structures can be observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation